The Role of Pancasila and Citizenship Education Teachers in Multicultural Education in Schools - Irvan Mahendra (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Background: The aim of this research was to find out and explain the role of Pancasila and citizenship education teachers in multicultural education. The method belonged to a library research approach. The data collection technique in this research was documentation, namely looking for data regarding variables in the form of books, papers, articles, journals, and so on. The data analysis technique used in this research was the descriptive method,namely research that seeks to describe and interpret what exists, opinions that are growing, ongoing processes, consequences or effects that occur or developing tendencies regarding the idea of ​​the role of Pancasila and citizenship education teachers in multicultural education in schools. The research results showed that the role of Civics teachers is very important in providing multicultural education considering that multicultural education is very important for students who live in a multicultural environment like the Indonesian nation. This helps students used a positive self-concept by providing an understanding of multicultural education, where Civics teachers must have a multicultural education perspective before they teach to students. This is a real challenge for professional Civics teachers. Teachers must be confident and ready to provide multicultural education.